Clinical and epidemiological study of human Bartonellosis at Monzon Valley, Huamalies, Huanuco - Tejada, Abelardo (2003)
Objective: To study human bartonellosis cases at Monzon valley and to determine the Lutzomyia species that may play a role in the transmission of the disease in the area. Material and methods: Carrion’s disease cases were studied at the deep jungle Monzon valley, Huamalies province, Huanuco, where and epidemic outbreak occurred between 1997 and 1998. Diagnosis was done by blood smear, culture and serology. CDC light traps and Shan-non trap in intra y peridomiciliary ambient were used for phlebotominae sandflies capture. Results: At 21 places the disease affected 140 people, 25 between 1 and 4 year-old, 81 women and 59 men; 121 presented the acute phase of the disease, 16 the intercalar phase and 3 the eruptive phase. The area population cutivates coca, coffee and cacao. Conclusion: Monzon valley is a new endemic area of human bartonellosis where transmission is mainly in intra and peridomiciliary ambient, and Lutzomyia serrana is the most probable vector.